2019
DOI: 10.1159/000502376
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Impact of Obesity, Metabolic Syndrome, Insulin Resistance, and Microbiome on the Diagnosis of Barrett’s Esophagus

Abstract: Background and Aim: The etiology and pathogenesis of Barrett's esophagus (BE) have been widely studied during recent decades. However, the association between BE and possible risk factors, including abdominal obesity (AO), metabolic syndrome (MetS), insulin resistance (IR), and the microbiome has not reached a consensus and lacks a systematic assessment. The purpose of our study is to evaluate, quantify, and summarize the association between these factors and BE risk. Methods: A systematic search of Pubmed, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Our MR study was consistent with the findings of previous observational studies that obesity was an independent risk factor for BE. A meta-analysis including 119,273 subjects found that abdominal obesity was significantly associated with the risk of BE 37 , which mutually confirmed the causal relationship between larger waist circumference and the risk of BE in the current study. Another case-control study using abdominal CT further elucidated that visceral abdominal fat was more strongly associated with BE rather than subcutaneous fat 3 .…”
Section: Discussionsupporting
confidence: 87%
“…Our MR study was consistent with the findings of previous observational studies that obesity was an independent risk factor for BE. A meta-analysis including 119,273 subjects found that abdominal obesity was significantly associated with the risk of BE 37 , which mutually confirmed the causal relationship between larger waist circumference and the risk of BE in the current study. Another case-control study using abdominal CT further elucidated that visceral abdominal fat was more strongly associated with BE rather than subcutaneous fat 3 .…”
Section: Discussionsupporting
confidence: 87%
“…MetS has been associated with cirrhosis, 251 colorectal adenomas, 252 acute pancreatitis, 253 and Barrett esophagus. 254…”
Section: Complicationsmentioning
confidence: 99%
“…MetS has been associated with cirrhosis, 252 colorectal adenomas, 253 acute pancreatitis, 254 and Barrett esophagus. 255…”
Section: Metabolic Syndromementioning
confidence: 99%